Peningkatan Sikap Peduli Lingkungan pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Melalui Implementasi Pendekatan Sains Teknologi Masyarakat (STM) di Madrasah Ibtidaiyah Salamah - Abel Tri Fatimah; Syahran Jailani (Lembaga Pengembangan Kinerja Dosen, 2025)
Environmental awareness is an effort to preserve, prevent damage to, and restore natural conditions. This attitude can be instilled through the integration of environmental values in science learning. The Science-Technology-Society (STS) approach is one effective method that fosters students' thinking skills and scientific literacy in line with technological and scientific developments. This study aims to determine whether environmental awareness in science subjects can be improved through the STS approach at MI Salamah in Jambi City, and to describe the implementation of the STS approach in enhancing environmental awareness in science subjects at the school. This research is a classroom action research using the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes two meetings with four stages: planning, implementation, observation, and reflection. The research results show an increase in students' environmental awareness attitudes in both Cycle I and Cycle II. In Cycle I, the average score for environmental awareness attitudes rose from 60.10% to 76.63%, while in Cycle II, it increased more significantly from 88.58% to 92.6%. In addition, test results also showed a significant improvement in students' understanding of the material. The implementation of the Science-Technology-Society (STS) approach in enhancing environmental awareness in science subjects at MI Salamah has been effective. It was applied through experiential learning, discussions, and creative activities that actively involved students in understanding and applying environmental concepts.